Acupuncture ameliorates breast cancer-related fatigue by regulating the gut microbiota-gut-brain axis - Lv, Zhuan; Liu, Ruidong; Su, Kaiqi; Gu, Yiming; Fang, Lu; Fan, Yongfu; Gao, Jing; Ruan, Xiaodi; Feng, Xiaodong (Frontiers in Endocrinology, 2022)
Cancer-related fatigue (CRF) is the most common side effect after chemotherapy for breast cancer (BC). Acupuncture treatment has an anti-fatigue effect and can regulate gut microbiota disturbance in fatigue patients. Related studies have shown that the gut microbiota-gut-brain axis is closely related to the occurrence of CRF. In this study, we first investigated the alterations of acupuncture on fatigue-like behaviour, gut microbiota, gut inflammation and neuroinflammation response, gut barriers, HPA axis and serum metabolomics in CRF mice after BC chemotherapy. Then, the correlation analysis of gut microbiota and other indicators was discussed. Our results showed that acupuncture treatment could exert an anti-fatigue effect and ameliorate the gut barrier, gut inflammation, neuroinflammation and dysfunction of the HPA axis in CRF mice after chemotherapy for BC. 16S rRNA sequencing showed that acupuncture treatment could enhance the abundances of Candidatus Arthromitus, Lactobacillus and Clostridia_UCG-014_unclassified and decrease the abundances of Escherichia-Shigella, Burkholderia-Caballeronia-Paraburkholderia and Streptococcus. Serum metabolomics analysis showed that acupuncture treatment could regulate the differential metabolites N-methylnicotinamide, beta-glycerophosphoric acid, geranyl acetoacetate, serotonin and phenylalanine, tyrosine and tryptophan biosynthesis, taurine and hypotaurine, and beta-alanine metabolic pathways. Correlation analysis indicated that there are certain correlations between gut microbiota and gut inflammation, neuroinflammation, gut barrier, HPA axis function and serum metabolites. In conclusion, our findings revealed that the anti-fatigue mechanism of acupuncture treatment may be closely related to the gut microbiota-gut-brain axis. This study also provides a new reference for basic and clinical research on CRF after breast cancer chemotherapy.